The Instruction of Lao Language for Grade 1 of Nan District Primary School, Luangprabang Province, Academic year 2024-2025 - KHAMPADITH, Shaidan; PHAIGNAVONG, Somchay; CHANHTHAHONG, Khamxay; MOUNGKHOUNSAVAT, Phoutthasay; PHATTHANA, Bounyong (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research was intended to study the instruction of Lao language for Grade 1 of Nan District Primary School, Luangprabang Province, Academic year 2024-2025, which aimed to investigate the instruction of the Lao language for Grade 1. Implementing the curriculum, teaching-learning activities, using instructional materials, measuring and evaluating, and providing facilities are all included in the study framework. It's a quantitative investigation. The 73 participants in the samples were principals and teachers in the primary school. Descriptive statistics and data collection were conducted using questionnaires. To ascertain the means and standard deviation, they were employed in the data analysis process. A case study of primary schools in the Nan district revealed that teachers follow manuals, teach four skills, organize student-centered teaching, use modern media, and provide a secure learning environment.